2023
DOI: 10.3390/ijerph20054372
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Emergency of Distant Tertiary Education in the Southern Region of Bangladesh during COVID-19: Policy Implication

Abstract: Many fields have been affected by COVID-19, including education. The pandemic has prompted a change in education due to the requirement for social distancing. Campuses are now closed in many educational institutions across the globe, and teaching and learning are now conducted online. Internationalization has significantly slowed down. A mixed-method study was designed for this research, with the goal of ascertaining the impact of COVID-19 on Bangladeshi students enrolled in higher education during and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Numerous studies have found a positive relationship between GHRM and job pursuit intention of university students' JPI (Zaid et al 2018, Jyoti 2019, Ghouri et Many studies have shown that corporate social responsibility (CSR) refers to a company's behavior towards its societal and stakeholder duties. This involves incorporating social requirements into commercial operations to benefit the company and society (Freitas et al 2020, Gazi et al 2023. CSR is an important part of a company's success, and the way a company does CSR affects job seekers' expectations of career success (Raza and Khan 2022).…”
Section: Hypotheses Development 221 Green Human Resource Management (...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have found a positive relationship between GHRM and job pursuit intention of university students' JPI (Zaid et al 2018, Jyoti 2019, Ghouri et Many studies have shown that corporate social responsibility (CSR) refers to a company's behavior towards its societal and stakeholder duties. This involves incorporating social requirements into commercial operations to benefit the company and society (Freitas et al 2020, Gazi et al 2023. CSR is an important part of a company's success, and the way a company does CSR affects job seekers' expectations of career success (Raza and Khan 2022).…”
Section: Hypotheses Development 221 Green Human Resource Management (...mentioning
confidence: 99%
“…CSR, GHRM, and an organization's reputation can help keep employees by making them more likely to look for work. A UK survey showed that high-achieving graduates consider the environmental situation, company performance, and reputation when applying for employment (Raza et al 2021, Gazi et al 2023. GHRM is vital for firms that want to strengthen their environmental sustainability and reputation (Afum et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The more convenient digital payments allows for a shift in the nature of the banking industry based on the client's mood. Using mobile banking which is widely used by clients, banks are starting to expand their operations (Palani and Yasodha, 2012;Gazi et al, 2023). Bangladesh is a developing country; the banking system of this country has been established on a strong basis in the last 51 years.…”
Section: Introductionmentioning
confidence: 99%